2021
DOI: 10.3390/ijerph18073523
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Occupational Stress and Presenteeism: The Mediating Role of Public Service Motivation and the Moderating Role of Health

Abstract: Presenteeism not only poses an economic cost to organizations but also generates reduced work efficiency and quality. The purpose of this study was to examine the connections between occupational stress, public service motivation (PSM), health, and presenteeism. A total of 981 nurses from 109 public hospitals in Jilin Province in China were enrolled in our study. Model 5 in the PROCESS micro was employed in order to verify the mediating effect of PSM and the moderating effect of nurses’ health on the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
2
8
3
Order By: Relevance
“…The nurses in the study indicated that even though they knew they were not at 100%, it was more prevalent for them to go to work sick, for reasons such as the high workload, not leaving their colleagues alone, low staffing levels, etc., all of which have been confirmed in other studies [ 22 , 23 , 24 , 25 , 26 ]. Our extensive questionnaire, with well identified factors, has made it possible to collect all the causes and reasons that lead nurses to come to work or to stay at work even when they are not feeling well, thus allowing us to obtain a very complete view of the phenomenon, which is useful for carrying out policies of care and attention to nurses [ 1 , 2 , 3 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The nurses in the study indicated that even though they knew they were not at 100%, it was more prevalent for them to go to work sick, for reasons such as the high workload, not leaving their colleagues alone, low staffing levels, etc., all of which have been confirmed in other studies [ 22 , 23 , 24 , 25 , 26 ]. Our extensive questionnaire, with well identified factors, has made it possible to collect all the causes and reasons that lead nurses to come to work or to stay at work even when they are not feeling well, thus allowing us to obtain a very complete view of the phenomenon, which is useful for carrying out policies of care and attention to nurses [ 1 , 2 , 3 ].…”
Section: Discussionsupporting
confidence: 83%
“…On account of all the above reasons, many nurses decide to go to work despite not being at 100% of their capacity and, hence, there may be a relation between presenteeism and reduced patient safety (although no studies have explicitly related these issues). This is because the errors that are made in healthcare frequently involve professionals who are in direct contact with the patient, where physiological problems such as lack of sleep, fatigue, suffering from some kind of illness (acute or chronic), and/or taking medication, bear a relation with the errors made [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nurses with a high level of job embeddedness tend to attach great importance to organizational interests, keep high organizational loyalty ( 39 ), and aim to maximize benefits for the organization. Hence, they might be keenly aware of the dark side of presenteeism, a negative work state that would lead to depletion of work capacity and loss of organizational productivity ( 54 ), and thus, avoid its occurrence. In general, individuals' job crafting would increase their job embeddedness, which would result in having higher organizational loyalty and tighter organizational ties, and thus, further influence them to avoid conducting presenteeism to maintain organizational interests.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies are currently examining how the pandemic is changing work conditions and affecting several job-related outcomes [ 17 , 49 , 50 , 51 ]. Among them, some authors have pointed out that both EI and social support have a strong impact in mitigating negative job-related outcomes.…”
Section: Introductionmentioning
confidence: 99%